Globalisation and poverty : threat or opportunity? - Fei, Jenny Sufen (2008)
This paper argues that globalisation presents a threat rather than an opportunity to poverty. This paper explores the effect of globalisation on poverty and examines why some countries in the developing world are being left out from reaping the benefits that globalisation brings. It also looks at the creation of the new poor in the developed world and how poverty is not only confined to the Third World as many would believe.